Grand stand 4 : design for trade fair stands - McNamara, Carmel; van Rossum-Willems, Marlous (Amsterdam : Frame Publishers, 2013)
Contains a varied selection of trade fair stands from all over the world. In this title, 150 cases will be presented on two to six pages each with an explanatory text about the concept and design, project credits, project photography and construction visuals. It also includes an index of designer profiles and contact details of stand constructors
boek